AB0452 Changes in Lipoproteins Associated with Tocilizumab Treatment Do not Influence the Atherogenic Index of Plasma of Rheumatoid Arthritis Patients. (9th June 2015) - Cacciapaglia, F.; Maria Grazia, A.; Rinaldi, A.; Scioscia, C.; Lopalco, G.; Covelli, M.; Iannone, F.; Lapadula, G.
Abstract : Background: Interleukin-6 inhibition by tocilizumab (TCZ) has been associated with changes in the lipoprotein profile [1], which could adversely impact cardiovascular (CV) risk in patients with rheumatoid arthritis (RA) [2]. Objectives: The aim of this observational study is to evaluate the effect of TCZ on lipoproteins and on the atherogenic index of plasma (AIP), a useful predictor of cardiovascular risk [3]. Methods: Forty patients (36 female; age 55±11 yrs) with active RA and an inadequate response to DMARDs treated with 8 mg/kg TCZ every 4 weeks intravenously, were consecutively enrolled with a 1 year follow-up. Patients on hypolipidemic therapy were excluded. Before and on week 12, 24 and 52, DAS28 and CDAI were evaluated, and blood samples were taken to assess plasmatic levels of total cholesterol (TC), low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, triglycerides (TG), and to calculate the AIP (LogTG/HDL). Results: During the first 24 weeks of TCZ treatment we observed a progressive increase of about 10% for TC and TG, and of about 30% for LDL-C and HDL-C compared to baseline. In the subsequent 6 months there was a reduction of TC and TG, whereas HDL-C and LDL-C continued to increase to about 40% compared to baseline (see Table). Lipid changes were inversely correlated with both the disease activity scores DAS28 and CDAI. Contextually the AIP was stable around 1, with no statistically significant changes. During the observational period no CV events have been observed. Conclusions: TCZ acts on the lipid profile increasing all the lipoprotein fraction, especially during the first 6 months of treatment, probably by a direct hepatic effect [4]. On the contrary the net effect of TCZ on AIP, and consequently on CV risk, would seem to be irrelevant. References: Kawashiri SY et al. Rheumatol Int. 2011 Souto A et al. Arthr Rheumatol 2015 Gasevic D et al. Lipids Health Dis. 2014 Strang AC et al. Atherosclerosis 2013 Disclosure of Interest: None declared